1998
DOI: 10.1016/s0022-5347(01)63748-0
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Testicular Injury From External Trauma: Evaluation of Semen Quality and Endocrine Parameters

Abstract: While the testicular salvage group had no significant seminal or endocrine abnormality, the orchiectomy group had a significant decrease in sperm density and elevation of baseline FSH and LH. These preliminary data suggest that testicular salvage is more protective of overall testicular function than orchiectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 10 publications
1
30
1
2
Order By: Relevance
“…Moreover, in normal men, administration of a large dose of rhFSH that resulted in an approximately 7-fold increase in circulating concentration of the gonadotropin elicited only a fold increase in plasma inhibin B levels (208). Although unilateral orchidectomy in men (see above) is usually associated with elevated FSH secretion, in contrast to the monkey, the hypersecretion of gonadotropin was not restricted to FSH (151,(153)(154)(155).…”
Section: Regulation Of Fsh Secretionmentioning
confidence: 99%
“…Moreover, in normal men, administration of a large dose of rhFSH that resulted in an approximately 7-fold increase in circulating concentration of the gonadotropin elicited only a fold increase in plasma inhibin B levels (208). Although unilateral orchidectomy in men (see above) is usually associated with elevated FSH secretion, in contrast to the monkey, the hypersecretion of gonadotropin was not restricted to FSH (151,(153)(154)(155).…”
Section: Regulation Of Fsh Secretionmentioning
confidence: 99%
“…Mais dans les traumatismes graves, il existe un pourcentage non nĂ©gligeable d'orchidectomie totale ou d'atrophie secondaire, reprĂ©sentant environ 10 % des patients dans la littĂ©rature adulte [11,13,16]. En 1998, Lin et al ont Ă©tudiĂ© l'impact des traumatismes testiculaires unilatĂ©raux sur la fertilitĂ© [24] : sur 67 patients recrutĂ©s de 1979 Ă  1995, dix ont pu ĂȘtre Ă©valuĂ©s sur le plan endocrinien et spermatique. Parmi les sept patients ayant eu une orchidectomie unilatĂ©rale, ils ont montrĂ© la survenue possible de petites anomalies, dans les limites de la normale, avec une diminution de la concentration moyenne des spermatozoĂŻdes et des taux de FSH-LH significativement augmentĂ©s (p < 0,01).…”
Section: Discussionunclassified
“…Changes in gonadal function after orchiectomy were also reported in patients with testicular injury. Lin et al [14] reported signiÂźcantly high FSH and LH levels after orchiectomy following testicular injury. And our previous report demonstrate d decrease in sperm concentration after orchiectomy due to testicular injury [20].…”
Section: Discussionmentioning
confidence: 99%